Експериментальне дослідження силових характеристик та якості гвинтового ромбічного домкрата - Попов, Станіслав Вячеславович; Popov, Stanislav (Запоріжжя: ТДАТУ, 2025)
UA: Гвинтові ромбічні домкрати є поширеними механізмами для підйому транспортних засобів у побутових та ремонтних умовах. Визначення їхніх силових характеристик та якості є важливим для оцінки технічного стану, ефективності конструкції та можливостей подальшого вдосконалення. У зв’язку з тим, що пряме вимірювання навантажень на домкрат потребує складного обладнання, доцільним є застосування непрямих методів, зокрема через момент, прикладений до рукоятки. Для експериментального визначення силових характеристик ромбічного гвинтового домкрата було проведено серію вимірювань крутного момен-ту на рукоятці за допомогою динамометричного адаптера. /// EN: Screw scissor jacks are widely used for lifting vehicles due to their simple design, compact dimensions, and affordable cost. However, the actual force characteristics of such jacks in real operating conditions may differ from the technical data declared by the manufacturer, which directly affects safety, reliability, and service life. This paper proposes a practical approach to determining the force characteristics and assessing the manufacturing quality of a mechanical scissor jack by measuring the torque applied to the handle using an accessible dynamometric adapter, the Shahe ANC-340.Experimental measurements were carried out, and based on the obtained data, the forces acting on the jack, the load on the lead screw, and the working pressure in the trapezoidal thread – an essential indicator of operability and wear resistance – were calculated. Additionally, graphical dependencies were built to illustrate the influence of vehicle lifting height, the angle between the jack's links, and the applied torque on the key force parameters.The results showed that the maximum force occurs when the wheel is lifted off the ground, followed by a decrease due to the redistribution of the vehicle’s mass. An inverse relationship between the opening angle of the mechanism and the load on the screw was observed, as well as a linear relationship between the working pressure in the thread and the torque on the handle. This confirms the effective transfer of force through the jack’s design without significant losses. The obtained data demonstrate the proper manufacturing quality of the investigated jack and confirm its suitability for safe use.The proposed method is simple, affordable, and can be applied in educational, laboratory, and field conditions to quickly verify technical characteristics, enhancing the safety and reliability of lifting mechanisms.
Experimental study of force characteristics and quality of a screw scissor jack
Keywords: домкрат ромбічний; висота підйому; висота підхвату; гвинт; різьба трапецієподібна; ванта-жопідйомність; сила; момент; тиск; адаптер динамометричний; scissor jack; lifting height; pickup height; screw; trapezoidal thread; load capacity; force; torque; pressure; dynamometric adapter